Victorian glassworlds : glass culture and the imagination 1830-1880 - Armstrong, Isobel (ACLS Humanities E-Book., 2008)
Isobel Armstrong's startlingly original book tells the stories that spring from the mass-production of glass in nineteenth-century England. Moving across technology, industry, local history, architecture, literature, print culture, the visual arts, optics, and philosophy, it will transform our understanding of the Victorian period. - ;Isobel Armstrong's startlingly original and beautifully illustrated book tells the stories that spring from the mass-production of glass in nineteenth-century England. Moving across technology, industry, local history, architecture, literature, print culture, the.